Effect of light-curing units on microleakage under dental composite resins - Queiroz, R. S. [UNESP]; Bandeca, Matheus Coelho [UNESP]; Calixto, L. R. [UNESP]; Saade, E. G. [UNESP]; Nadalin, M. R.; Andrade, M. F. [UNESP]; Porto-Neto, S. T. [UNESP] (Maik Nauka/interperiodica/springer, 2009)
The aim of this study was to determine the effect of two light-curing units (QTH and LED) on microleakage of Class II composite resin restorations with dentin cavosurface margins. Twenty extracted mandibular first premolars, free of caries and fractures were prepared two vertical slot cavities in the occluso-mesial and -destal surfaces (2 mm buccal-lingually, 2 mm proximal-axially and cervical limit in enamel) and divided into 4 equal groups (n = 8): GI and GII: packable posterior composite light-activated with LED and QTH, respectively; GIII and GIV: micro-hybrid composite resin light-activated with LED and QTH, respectively. The composite resins were applied following the manufacturer's instructions. After 24 h of water storage specimens were subjected to thermocycling for a total of 500 cycles at 5 and 55A degrees C and the teeth were then sealed with impermeable material. Teeth were immersed in 0.5% Basic fuchsin during 24 h at room temperature, and zero to three levels of penetration score were attributed. The Mann-Whitney and Kruskal-Wallis tests showed significant statistically similar (P > 0.05) from GI to GII and GIII to GIV, which the GII (2.750) had the highest mean scores and the GIII and GIV (0.875) had lowest mean scores. The use of different light-curing units has no influence on marginal integrity of Class II composite resin restorations and the proprieties of composite resins are important to reduce the microleakage.